The limit of inconsistency reduction in pairwise comparisons - Koczkodaj, Waldemar W.; Szybowski, Jacek (Zielona Góra: Uniwersytet Zielonogórski)
This study provides a proof that the limit of a distance-based inconsistency reduction process is a matrix induced by the vector of geometric means of rows when a distance-based inconsistent pairwise comparisons matrix is transformed into a consistent PC matrix by stepwise inconsistency reduction in triads. The distance-based inconsistency indicator was defined by Koczkodaj (1993) for pairwise comparisons.
Keywords: pairwise comparison; inconsistency reduction; convergence limit; decision making